Effects of Passive Hydrotherapy WATSU (WaterShiatsu) in the Third Trimester of Pregnancy: Results of a Controlled Pilot Study. (1st March 2015) - Schitter, Agnes M.; Nedeljkovic, Marko; Baur, Heiner; Fleckenstein, Johannes; Raio, Luigi
Abstract : Background . WATSU (WaterShiatsu) is a complementary therapeutic treatment method comprising passive stretches and massage techniques administered in 35°C warm water. Pregnant women claim safe methods to reduce pain, stress, and fatigue. Therefore, we conducted a pilot study evaluating the effects of WATSU on pregnancy-related complaints in third trimester pregnant women. Methods . Nine healthy pregnant women at gestational week ≥34 were included in an intervention group (receiving WATSU) and compared to eight women in a passive control group (receiving no treatment). WATSU was performed on days 1 and 4 of the study, accompanied by ultrasound examinations. Outcomes include physiological and psychometric as well as qualitative data. Participants in the control group completed questionnaires only. Results . WATSU was found to significantly lower participants' levels of stress and pain and to improve their mental health-related quality of life and mood. In comparison to the passive control group, participants in the intervention group reported reduction in perceived stress from day 1 to day 8 (P = 0.036, Cohen'sf = 0.57 ). Qualitative data indicate that WATSU was appreciated as enjoyable and deeply relaxing. No negative side effects were reported. Conclusion . Our findings support the notion that WATSU yields therapeutic benefits for pregnant women and warrant further research. This study has been registered at ClinicalTrials.gov:NCT01708018 .